Two new species of the Euconnus taiwanus group from Zhejiang, China (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2023)
The recently established Euconnus taiwanus group within Euconnus s. str. includes six species known to inhabit Taiwan, China and Japan. Two more members of this group are described based on specimens collected in eastern China (Zhejiang Province): E. (s. str.) bibaculoides sp. n., and E. (s. str.) mimicus sp. n.